Factors Associated with Early Reoperations Following Cranial and Spinal Neurosurgery in a Tertiary Care Center in Nepal - Regmi, Prakash; Pradhanang, Amit Bahadur; Sedain, Gopal; Shilpakar, Sushil Krishna; Sharma, Mohan Raj (Nepal Journal of Neuroscience, 2024)
Background: Complications following neurosurgical procedures often lead to reoperations, resulting in poor outcomes and increased healthcare costs. Reoperation rates can serve as a quality indicator for surgical care. This study aimed to analyze factors associated with unplanned reoperations after cranial and spinal surgeries. Objective: To identify factors contributing to early reoperations within 30 days of cranial and spinal neurosurgical procedures. Methods: We retrospectively analyzed data from patients who underwent cranial or spinal surgeries at a tertiary care hospital between 2019 and 2023. Patients requiring unplanned reoperations within 30 days were included. Statistical analysis was performed using SPSS version 27. Results: A total of 3880 patients were operated and the reoperation of 64 patients were analyzed, with a mean age of 38.5 years (range:1-72). The reoperation rate was 1.6%. Most patients were adults, and there was a female predominance. The majority of reoperations occurred within the first seven days after the initial surgery. The most common reason for reoperation were hematoma formation. Hematoma evacuation and decompressive hemicraniectomy were the most frequently performed reoperations. Conclusion: This study highlights the importance of identifying risk factors and improving perioperative care to reduce early reoperations. The findings emphasize the need for close postoperative monitoring during the critical first seven days to enhance patient outcomes and optimize healthcare resources